First Three Cal Poly Buildings (1905)
The first three buildings at the California Polytechnic School, designed by architect William Weeks. Administration Building, Center, Dormitory No. 1 on the right and the Household Arts Building on the left, under construction. The household arts building was constructed in 1906. Photo can also be found here: http://digital.lib.calpoly.edu/rekl-3940